A path model linking health literacy, medication self-efficacy, medication adherence, and glycemic control. Issue 11 (November 2018) - Huang, Yen-Ming; Shiyanbola, Olayinka O.; Chan, Hsun-Yu
Highlights: Medication self-efficacy mediates the relationship between numeracy and medication adherence. Individuals with higher numeracy skills may develop a greater level of medication self-efficacy. Greater self-efficacy may result in a higher diabetes medication adherence and a lower hemoglobin A1c. Improvement in numeracy skills and self-efficacy is recommended to enhance medication adherence. Abstract: Objective: To investigate whether medication self-efficacy moderates or mediates the relationship between health literacy and medication adherence. To propose a path model that illustrates the interrelated relationship between health literacy, medication self-efficacy, medication adherence, and hemoglobin A1c (HbA1c). Methods: This cross-sectional study was performed via a face-to-face survey. Factors that may influence medication adherence and HbA1c were identified from the literature review. One hundred and seventy-four participants included were ≥20 years old with diagnosed type 2 diabetes, understood English, and were prescribed at least one oral diabetes medicine. During clinic visits, a questionnaire was administered to evaluate health literacy, medication self-efficacy, and medication adherence. HbA1c values were obtained from electronic medical records. Path analyses were conducted for data analysis. Results: Medication self-efficacy mediated but did not moderate the relationship between numeracy and diabetes medication adherence. Participants with higher numeracy skills may develop a greater level of medication self-efficacy, which in turn may result in a higher level of diabetes medication adherence and a lower level of HbA1c. Conclusion: Enhancing patients' medication self-efficacy and numeracy skills may be imperative in intervention programs to improve diabetes medication adherence. Practice implications: An improvement in numeracy skills and medication self-efficacy is recommended to enhance diabetes medication adherence.